Perlindungan Hukum Terhadap Konsumen dalam Kompilasi Hukum Ekonomi Syariah - Sirmaneli, Sirmaneli; Sonafist, Y; Helmina, Helmina; Putri, Saffa Azzahra (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2022)
The purpose of this study is to find out and understand the process of buying and selling goods online and to explain the legal protection of consumers against broken promises in the online sale and purchase of goods according to the Compilation of Sharia Economic Law (KHES). The type of research used in this study is qualitative research. The researcher concludes that the Compilation of Sharia Economic Law also provides legal protection for consumers who enter into sale and purchase agreements, although it does not specifically explain the legal force, but in book II KHES explains that if there is a default If the promise in a contract is confirmed by Article 38, the party who breaks the promise will be subject to sanctions.